영업권 손상차손 인식과 경영자 예측정보의 자발적 공시에 대한 연구 - 서영미(Youngmi Seo) (대한경영학회지, 2020)
본 연구는 2013년부터 2018년까지의 기간 동안 유가증권상장 및 코스닥상장 기업을 대상으로 영업권 손상차손의 인식이 경영자 예측정보의 자발적 공시에 미치는 영향을 살펴본다. 현행 회계기준 하에서는 영업권에대하여 매년 1회 이상 손상검사를 실시하여야 하며, 영업권을 포함한 현금창출단위의 장부금액과 회수가능액을비교하여 영업권 손상차손 인식 여부가 결정된다. 이 때 회수가능액은 순공정가치와 사용가치 중 큰 금액으로측정되는데, 회수가능액의 추정에 경영자의 상당한 주관적인 판단과 추정이 개입되기 때문에 영업권 손상차손인식 관련 의사결정은 경영자의 재량권이 행사되는 대표적인 항목 중 하나이다(Ball, 2006). 또한, 영업권 손상차손은 기업의 주가 및 미래 수익성 변화 등 기업 가치에 대한 정보를 전달하는 선행적인 지표이며, 기업 가치와유의한 음(-)의 관계를 가지고 있다. 따라서 영업권 손상차손 인식 관련 의사결정은 정보비대칭을 초래하고관련 정보수요를 증가시킬 수 있을 것이다. 한편, 경영자는 정보비대칭을 감소시키고 역선택의 문제 등을해소하기 위하여 기업 내부의 사적인 정보를 반영한 예측정보를 자발적으로 시장에 공시할 유인이 있다. 주요실증분석 결과는 다음과 같다. 첫째, 영업권 손상차손을 인식한 경우 경영자 예측정보를 자발적으로 공시하는것으로 나타났으며, 둘째, 영업권 손상차손의 크기가 경영자 예측정보의 자발적 공시에 미치는 영향을 분석한결과는 통계적으로 유의하지 않았다. 이러한 결과는 영업권 손상차손을 인식하는 경우 기업 가치에 부정적인영향을 줄 수 있는 사건이 발생하고, 경영자의 재량적인 판단에 대하여 기업 내·외부의 정보비대칭이 발생하여관련 정보수요가 증가하게 되므로 경영자는 기업 내부의 사적인 정보를 반영한 예측정보를 시장에 적극적으로전달하여 정보비대칭을 감소시키고자 할 가능성이 있음을 시사한다. 본 연구는 경영자 예측정보의 자발적공시 요인으로서 영업권 손상차손의 인식이라는 새로운 요소를 제시하고 있다는 점에서 의의가 있으며, 영업권손상차손 관련 선행연구의 대부분이 영업권 손상차손 인식 관련 의사결정에 재량적인 특성 자체에 초점을맞추고 있는 반면 본 연구에서는 영업권 손상차손 인식 관련 의사결정이 대표적인 또 다른 재량적인 의사결정중 하나인 경영자 예측정보의 자발적 공시에 미치는 영향을 살펴보았다는 점에서 공헌점이 있다. Using a comprehensive data set of listed firms for the period of 2013-2018, this study examines the association between goodwill impairment and voluntary disclosures of management forecasts. The impairment-only approach under International Financial Reporting Standards (IFRS) requires to test goodwill for impairment at least annually or whenever there is an indication that the goodwill might be impaired. To test for an impairment loss, firms compare the recoverable amount of cash-generating unit and the carrying value of it, and the recoverable amount is defined as the higher of fair value less costs of disposal and its value in use. As market prices are not available in the majority of goodwill impairment valuation situations, it is necessary to forecast future cash flows and determine applicable discount rates to measure value in use. Hence, goodwill impairments depend on management’s subjective estimates. Goodwill impairment is expected to convey private information but agency theory presumes that management is likely to take advantage of subjectivity inherent in the impairment test procedure and exerts the discretion opportunistically. Management forecasts represent a key voluntary disclosure mechanism through which managers communicate the private information to market participants. This study finds that firms that recognize goodwill impairments issue more management forecasts than firms that report no goodwill impairments. However, the magnitude of goodwill impairments does not affect the disclosure patterns of management forecasts. The results indicate that voluntary disclosures of management forecasts are used to alleviate information asymmetry due to the recognition of goodwill impairments. This study contributes to the literature that demonstrates the incentives of voluntary disclosure of management forecasts. This study documents that goodwill impairments can be one of the factors that affect managers’ decisions to voluntarily disclose forecasts. This study also advances the research on goodwill impairments by directly focusing on the effect of goodwill impairments on management forecasts that are likely to be subject to management discretion. KCI Citation Count: 0